2004
DOI: 10.1096/fj.03-0658fje
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous allergic contact dermatitis responses are diminished in mice deficient in neurokinin 1 receptors and augmented by neurokinin 2 receptor blockage

Abstract: Sensory neuropeptides such as neurokinin A (NKA) or particularly substance P (SP) by neurokinin receptor (NK-R) activation modulate skin and immune cells functions during neurogenic inflammation. In this study, we examined the relative importance of SP/NK-1Rs or NKA/NK-2Rs in a murine model for allergic contact dermatitis (ACD) and tested if the functional absence of NK-Rs will impair inflammatory response in vivo. Mice lacking NK-1Rs (C57BL/6J-NK-1R-/-) displayed a significantly reduced ACD inflammatory ear s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 58 publications
1
34
0
2
Order By: Relevance
“…In these experiments, SP activation of DC during the effector phase of a Th1-driven inflammation triggered a massive and rapid LC mobilization out of the epidermis and enhanced inflammation. An inflammation-promoting effect of SP signaling was also demonstrated in other Th1 and neurogenic inflammation-dominated neuroimmune constellations, such as during the elicitation of contact hypersensitivity (7,58,59), during provocation of AlD (32)(33)(34), in hair loss (60), and in healthy murine skin and lymphocytes (34,39,40). This effect appears to be further facilitated by stress-and nerve growth factor-induced plasticity of the peripheral nervous system and malfunctioning HPA responsiveness (32,34,39,61,62).…”
Section: Discussionmentioning
confidence: 90%
“…In these experiments, SP activation of DC during the effector phase of a Th1-driven inflammation triggered a massive and rapid LC mobilization out of the epidermis and enhanced inflammation. An inflammation-promoting effect of SP signaling was also demonstrated in other Th1 and neurogenic inflammation-dominated neuroimmune constellations, such as during the elicitation of contact hypersensitivity (7,58,59), during provocation of AlD (32)(33)(34), in hair loss (60), and in healthy murine skin and lymphocytes (34,39,40). This effect appears to be further facilitated by stress-and nerve growth factor-induced plasticity of the peripheral nervous system and malfunctioning HPA responsiveness (32,34,39,61,62).…”
Section: Discussionmentioning
confidence: 90%
“…Kinkelin et al [12] found no diVerence in the expression of dermal PGP 9.5-ir nerve Wbres in the contact eczematous skin compared to control skin. However, the expression of epidermal PGP Several reports have been published on the involvement of sensory neuropeptides in ACD [7,18,23]. Thus, the implication of these messengers in established ACD is evident and has earlier been documented.…”
Section: Discussionmentioning
confidence: 99%
“…Substance P and neurokinin A (NKA) are members of the tachykinin family that are known to be implicated in murine ACD [18]. Substance P and NKA have an agonizing eVect on preferentially neurokinin-1 (NK-1) receptor (R) and NK-2R, respectively [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In the skin, signaling through the NK1R with SP or NK1R agonists prevents cutaneous tolerance induced by UV-B light and favors delayed-type hypersensitivity (DTH) reactions through the release of IL-12p70, a potent Th1-biasing cytokine (19,23). Taken together, these observations highly suggest that signaling via the NK1R during the initiation of skin-mediated immune responses will favor development of Th1 effector immunity.…”
Section: E Fficient Vaccine Approaches For Tumors and Infectious Disementioning
confidence: 99%